BENTUK SEL EPIDERMIS, TIPE DAN INDEKS STOMATA 5 GENOTIPE KEDELAI PADA TINGKAT NAUNGAN BERBEDA - Sundari, Titik; Atmaja, Rahmat Priya (Perhimpunan Biologi Indonesia, 2011)
ABSTRACTShape of Epidermal Cells, Type and Stomata Index of 5 Soybean Genotypes at Different Levelsof Shading. This study aimed to determine the shape of epidermal cells, type of stomata andthe stomatal index of five soybean genotypes at different levels of shading. Research conductedat the Screen House of Indonesian Legumes and Tuber Crops Research Institute in Marchuntil July 2007. Split plot design with repeated three times was used in this research. The mainplots were four levels of shading (0%, 25%, 50% and 75%) and subplot is the five soybeangenotypes (Pangrango, Tanggamus, Wilis, Lokon and IAC-100). Shading is used black screen.Plants fertilized with the 50 kg Urea + 100 kg SP36 75 + 75 kg KCl / ha. Fertilizing done atplanting time. The results showed that shade does not change shape of epidermal cell andstomata types of five soybean genotypes. Differences in stomatal index was not determinedby interaction of genotypes with levels of shading, but by the differences in shade andgenotype. Shading treatment increased stomatal index of soybean abaxial leaf surface. HighestSomatal index of soybean abaxial leaf surface is achieved by IAC 100 and the lowest is achievedby Wilis. Wilis is a genotype that can be adapted to the shaded environment, by maintainingleaf area, number of epidermial cells and stomata, stomatal index, and seed weight.Key words : soybean, shading, epidermis and stoma